2021
DOI: 10.1210/jendso/bvab100
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Toxicity and Outcomes in Patients With Metastatic Malignancies Treated With Immune Checkpoint Inhibitors

Abstract: Context Immune checkpoint inhibitors (ICIs) have gained a revolutionary role in management of many advanced malignancies. However, immune-related endocrine events (irEEs), have been associated with their use. irEEs have non-specific clinical presentations and variable timelines, making their early diagnosis challenging. Objective To identify risk factors, timelines, and prognosis associated with irEEs development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Along with thyroid dysfunction, the impact of immune-related endocrine AEs on patient outcomes have also been investigated in 2 retrospective studies. 5,7 In a large retrospective analysis of 551 patients receiving nivolumab, atezolizumab, pembrolizumab, ipilimumab, or combination immunotherapy, endocrine toxicity most commonly occurred in those receiving ipilimumab monotherapy or a combination therapy containing ipilimumab. Time to immune-related endocrine effects was 9 weeks, and those developing endocrine toxicity demonstrated an improved overall survival (HR: 1.86, 95% CI: 1.39-2.49, P < .001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with thyroid dysfunction, the impact of immune-related endocrine AEs on patient outcomes have also been investigated in 2 retrospective studies. 5,7 In a large retrospective analysis of 551 patients receiving nivolumab, atezolizumab, pembrolizumab, ipilimumab, or combination immunotherapy, endocrine toxicity most commonly occurred in those receiving ipilimumab monotherapy or a combination therapy containing ipilimumab. Time to immune-related endocrine effects was 9 weeks, and those developing endocrine toxicity demonstrated an improved overall survival (HR: 1.86, 95% CI: 1.39-2.49, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have demonstrated improved outcomes for patients developing hypothyroidism from ICI therapy. [3][4][5]7 These studies were retrospective and included patients with advanced malignancy receiving multiple ICIs. In a study of 91 patients receiving atezolizumab or avelumab for various advanced malignancies, 21% developed new onset hypothyroidism defined as a TSH level higher than 4.3 µIU/mL and T4 level lower than 1.7 µIU/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have reported ICI-related endocrine toxicity, most of these data are derived from clinical trials (8,9), but there is short of data in real world.…”
Section: Introductionmentioning
confidence: 99%